Sperm Terminologies in Al-Qur’an and Andrology Perspective. - Hilmi Hasna Ardianti; Ayu Ida Rohani; Sri Nur Wahyuni; Ahmad Zaki Mubarak (Lembaga P3M STAI Persis Bandung, 2022)
Abstract[Sperm Terminologies in Al-Qur’an and Andrology Perspective] This article discusses sperm in the Qur'an in QS. An-Najm: 46 and al-Mu'minun: 13. Preliminary findings indicate that there is still a need for studies on andrology to encourage the importance of studies on this matter. This study uses a qualitative comparative study method with a literature review approach. The data source is the book